Township-level governance in disaster preparedness in Yangon, Myanmar, during the period of transformation from April 2011 to January 2021 - Zin Mar Than; Hlaing Maw Oo; Sophie-Bo Heinkel; Toe Aung; Tin Tin Kyi; Saw Sandar Oo; Win Lei Mar; Win Maung; Zin Nwe Myint; Khin Khin Soe; Marlene Willkomm; Christian Miller; et al. (Natural Hazards, 2026)
Since Cyclone Nargis hit the country in 2008, Myanmar has stepped up its efforts to implement a disaster management system aimed at reducing disaster risk. At the same time, a far-reaching political and social transformation took place, shifting from military to civilian administration between April 2011 and January 2021. During this period, new concepts for disaster risk management were developed internationally, focusing on local governance and community-based strategies. This article provides an overview of the legal and organisational framework introduced in Myanmar for disaster risk management during the transition phase. In particular, it examines how and to what extent governance elements have been integrated into the system to meet local societal needs. The focus is on identifying challenges, gaps and opportunities in local governance structures. The study employs a mixed-methods analysis approach. This involved conducting 28 expert interviews with Yangon-based disaster management institution members as well as a quantitative household survey of 896 people in eight Yangon townships. Additionally, an in-depth analysis of government documents and reports was conducted. The study shows that the general framework for implementing governance aspects was already well established when the political system changed again in 2021. In practice, however, governance aspects remain challenging.

Disaster preparedness and resilience at household level in Yangon, Myanmar - Sophie-Bo Heinkel; Benni Thiebes; Zin Mar Than; Toe Aung; Tin Tin Kyi; Win Lei Mar; Saw Sandar Oo; Christian Miller; Marlene Willkomm; Win Maung; Zin Nwe Myint; Khin Khin Soe; et al. (Natural Hazards, 2022)
Resilience has become important in disaster preparedness and response. Unfortunately, little is known about resilience at the household level. This study presents the results of a survey into individual and household level preparedness to disaster events in Yangon, Myanmar, which is prone to natural disasters such as tropical cyclones, flooding, and earthquakes. The study aimed to understand societal resilience and to provide information that could be used to develop a holistic framework. In four different Yangon townships, 440 households were interviewed. The results of the survey indicate how risk preparedness could be improved by specific measures related to the following five factors: (1) increasing the general public’s knowledge of first aid and its role in preparedness; (2) improving mobile phone infrastructure and capacity building in its usage so that it can be used for communication during disasters, along with building up a redundant communication structure; (3) better use and organisation of volunteer potential; (4) more specific involvement of religious and public buildings for disaster response; and (5) developing specific measures for improving preparedness in urban areas, where the population often has reduced capacities for coping with food supply insufficiencies due to the high and immediate availability of food, shops and goods in regular times. The findings of this survey have led to specific recommendations for Yangon. The identified measures represent a first step in developing a more general framework. Future research could investigate the transferability of these measures to other areas and thus their suitability as a basis for a framework.

Laboratory investigation on the compressibility of Singapore marine clays - Myint Win Bo; Victor Choa; Jian Chu; Arul Arulrajah; Suksun Horpibulsuk (Marine Georesources & Geotechnology, 2017)

Mineralogy and Geotechnical Properties of Ultrasoft Soil from a Nearshore Mine Tailings Sedimentation Pond - Myint Win Bo; Arul Arulrajah; Patimapon Sukmak; Suksun Horpibulsuk; Melvyn Leong (Marine Georesources & Geotechnology, 2016)

Step Loading Compression of Ultra-Soft Soil under Radial Drainage Conditions - Myint Win Bo; Kai Sin Wong; Victor Choa; Arul Arulrajah; Suksun Horpibulsuk (Marine Georesources & Geotechnology, 2016)

Ground Investigations for Changi East Reclamation Projects - Myint Win Bo; Ming-Fang Chang; A. Arulrajah; Victor Choa (Geotechnical and Geological Engineering, 2012)

Laboratory Validation of Ultra-Soft Soil Deformation Model - Myint Win Bo; Victor Choa; Kai Sin Wong; Arul Arulrajah (Geotechnical and Geological Engineering, 2011)